Comparison of the Effect of Multiple Dietary Supplements on the Quality of Sperm Parameters in Elite and Amateur Soccer Players - Saeid Rostami; Bijan Rajaeian; Nooshin Rajaeian (Journal of Nutrition and Metabolism)
Conclusion: Supplementation with Condensyl and Nurilia, which include key vitamins and antioxidants supporting the one-carbon cycle, significantly improves sperm motility and morphology in male football players. These findings support the use of such supplements as a supportive therapy in the management of male infertility.